Woolly cupgrass (Eriochloa villosa /Thunb./ Kunth), a recently occured invasive weed in Trans-Tisza Region and a trial for control in maize - Szilágyi, Arnold; Balogh, Zoltán; Dávid, István; Szabó, László; Radócz, László (Acta Agraria Debreceniensis, 2015)
To the effective control of invasive weeds are essential to prevent establish, if has already happened obstacle to massive accumulation, and promoting the efficient and rapid eradication, if it is possible. The Woolly cupgrass (Eriochloa villosa /Thunb./ Kunth) belongs to weeds which “hard to control” especially in corn. One of the difficulties of effective control is the prolonged emergence causing avoidance of several individuals the contact with pre-emergent herbicides. Another problem arises due to the intensive use of post-emergence herbicide products with short duration of action. To optimalize of timing of treatment is essential for successful control of later emerging weeds. The recently established Woolly cupgrass in Hungary shows resistance or reduced susceptibility to substantial portion of herbicides used in corn. The data collected from small-plot trials demonstrates that application of sulfonylurea or selective monoctyledonous herbicides can be effective against the Woolly cupgrass.